The use of confessionary evidence under the counter-terrorism laws of Sri Lanka : an interdisciplinary study - Chandrasekaram, Visakesa (Religion and society in Asia., 2017)
For more than three decades, the Liberation Tigers of Tamil Eelam (LTTE) fought a gruesome war for independence against the majoritarian Sinhalese government of Sri Lanka. Even as the government fought LTTE on the battlefield, it also pursued a legal war through the enactment of counterterrorism laws that permitted indefinite detention and the use of confessions as sole evidence. This book applies theoretical insights from the work of philosophers such as Carl Schmitt, Giorgio Agamben, and Michel Foucault to the Sri Lankan context to examine the conflicting narratives relating to these laws produced by both sides in the conflict.